An Improved Lyman‐Alpha Composite. Issue 12 (6th December 2019) - Machol, J.; Snow, M.; Woodraska, D.; Woods, T.; Viereck, R.; Coddington, O.
Abstract: The hydrogen Lyman‐alpha (Lyman α) line at 121.56 nm is the strongest solar vacuum ultraviolet emission line. Especially because of the impacts on planetary atmospheres, long‐term data sets of Lyman α are important for understanding solar and atmospheric processes. A revised composite data set of daily Lyman α values beginning in 1947 is constructed using measurements of Lyman α from Atmospheric Explorer E, Solar Mesospheric Explorer, Upper Atmosphere Research Satellite, and Solar Radiation and Climate Experiment. Gaps are filled using proxy models based on the Magnesium II index and the 10.7‐ and 30‐cm solar radio fluxes (F10.7 and F30). Plain Language Summary: When ultraviolet light from the Sun is absorbed in the Earth's upper atmosphere above 70 km, it can impact radio communications and satellite orbits. The brightest solar wavelength in the ultraviolet is called the Lyman‐alpha line and is emitted by hydrogen in the Sun's atmosphere. Because ultraviolet light is absorbed by the Earth's atmosphere, measurements of the Lyman‐alpha line must be made by satellites which are above most the atmosphere. This paper is about the development of a set of daily measurements of Lyman‐alpha brightness (irradiance) from 1947 through the present time. This data set will be used to validate other solar irradiance data, models of the Sun's variable intensity, and models of terrestrial atmospheric processes. Key Points: The hydrogen Lyman‐alpha line at 121.56 nm is the strongest solar vacuum ultraviolet emission line An improved composite data set of daily Lyman α values beginning in 1947 is constructed using satellite measurements The revised Lyman α data set is available with daily updates